Rooting potential of grapevine rootstocks cuttings - Wurz, Douglas André; Pires Feldberg, Nelson; Fontanella Brighenti, Alberto (Revista Ceres, 2022)
The objective of this work was to evaluate the rooting potential and propagation of seventeen grapevinevine rootstocks. The experiment was carried out in the municipality of Canoinhas - Santa Catarina, in 2018 and 2019. Woody canes from the grapevine rootstocks 99R, 110R, 420 A Mgt, 101-14 Mgt, IAC 766, IAC 313, IAC 572, Courdec 3309, Freedom, Gravesac, Harmony, Kober 5BB, Paulsen 1103, Salt Creek, Solferino, SO4 and VR043-43 were collected during dormancy period. After 45 days of the experiment installation, parameters considered as quality indicators were evaluated: percentage of rooting; average number and length of roots, number of leaves and length of branches. The results obtained were subjected to analysis of variance, and the means were grouped using the Scott-Knott test at 5% probability. The rootstocks showed different rooting behaviors, and it is concluded that 101-14 Mgt, IAC 572, Courdec 3309, Freedom, Gravesac, Harmony and Paulsen 1103 have greater rooting and propagation potential. While 110 R, 420 A Mgt and VR 043-43 present difficulties in propagation, due to low rooting, low number of roots and low average length of roots, requiring the use of exogenous auxin, in order to increase rooting rates.